2015
DOI: 10.1590/s1517-838246420140462
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rhodococcus erythropolis strain IBBPo1 to toxic organic solvents

Abstract: Recently, there has been a lot of interest in the utilization of rhodococci in the bioremediation of petroleum contaminated environments. This study investigates the response of Rhodococcus erythropolis IBBPo1 cells to 1% organic solvents (alkanes, aromatics). A combination of microbiology, biochemical, and molecular approaches were used to examine cell adaptation mechanisms likely to be pursued by this strain after 1% organic solvent exposure. R. erythropolis IBBPo1 was found to utilize 1% alkanes (cyclohexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Rhodococcus erythropolis is the most recommended bacterial species for real oil feed BDS because of its hydrophobicity, its broad versatile BDS ability over various recalcitrant alkylated DBTs, its efficient solvent and hydrocarbon resistance, and its emulsification capabilities through the generation of biosurfactants. This improves the mass transfer rate of the S compounds from the oil phase, enriches their bioavailability, and detaches the complementary desulfurized product from the cells towards the oil phase without affecting its hydrocarbon skeleton or the calorific value 31,54–58 . Yet, as far as the authors are aware, no BDS research studies have been reported using Rhodococcus jialingiae .…”
Section: Resultsmentioning
confidence: 99%
“…Rhodococcus erythropolis is the most recommended bacterial species for real oil feed BDS because of its hydrophobicity, its broad versatile BDS ability over various recalcitrant alkylated DBTs, its efficient solvent and hydrocarbon resistance, and its emulsification capabilities through the generation of biosurfactants. This improves the mass transfer rate of the S compounds from the oil phase, enriches their bioavailability, and detaches the complementary desulfurized product from the cells towards the oil phase without affecting its hydrocarbon skeleton or the calorific value 31,54–58 . Yet, as far as the authors are aware, no BDS research studies have been reported using Rhodococcus jialingiae .…”
Section: Resultsmentioning
confidence: 99%
“…strain DN22 ( Priestley et al, 2006 ; Solyanikova et al, 2017 ). Conversely, an increase of the cell size was reported with R. erythropolis strain IBBPo1 grown on aromatics ( Stancu, 2015 ) in parallel with the accumulation of intracellular electron-transparent inclusion bodies, which are typically hydrophobic compounds with a storage function ( Alvarez et al, 1996 ). Similar electron-transparent inclusions were visible in BCP1 cells grown on MSM with glucose, while CHCA-grown BPC1 cells exhibited prominent electron-dense inclusion bodies, one or two granules per cell near the DNA containing region ( Figure 3 and Supplementary Figure S2 ), which were smaller and less evident in CPCA-grown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, carotenoids were suggested to have an antioxidant role in Rhodococcus cells grown as biofilm, whose development could induce an oxidative stress in individual cells within the community due to an increase of reactive oxygen species (ROS) levels (Zheng et al 2013 ; Kundu et al 2015 ). Rhodococcus erythropolis IBBPo1 cells exposed for 1 or 24 h to 1% alkanes instead showed a modification of the carotenoid profile with an increased level of lycopene (the intermediate in the biosynthesis of γ-carotene and β-carotene) as compared to the control, likely as a response to these organic solvents (Stancu 2015 ). Lastly, carotenoid formation in a Rhodococcus strain isolated from Azolla symbiotic cavities was reported to be induced by cells’ exposition to the light, which led to a sevenfold higher accumulation of a yellowish-orange pigment than dark-incubated cells (Cohen et al 2004 ).…”
Section: Carotenoidsmentioning
confidence: 99%
“…In this respect, a few studies have reported the capacity of Rhodococcus spp. strains to accumulate carotenoids growing on hydrocarbon and nitroaromatic compounds (Table 1 ) (Stancu 2015 ; Kundu et al 2015 ).…”
Section: Carotenoidsmentioning
confidence: 99%